2021
DOI: 10.11648/j.edu.20211001.15
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Parental Involvement and Parents’ Level of Education on Student’s Academic Accomplishment

Abstract: Parental involvement in school has been demonstrated to play a crucial role in children's academic achievement.This article examines the relation of adolescent's academic achievement to parental involvement and parent's education level, separately, grounded on a quantitative approach. All participants were middle-class dual-earner parents from eight cities across the United States. Spearman's correlation coefficient was used to find out if adolescent academic performance is correlated with parental involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Students become critical thinkers when they encounter discussions on home-related studies. Researchers have consistently demonstrated a strong correlation between the educational outcomes of parents and those of their children (Lim, 2021). However, Correlation cannot define the cause of performance; other factors like parental support, a conducive home learning environment, access to resources such as technology, and extra-curricular activities can be the foundation and cause of students' academic achievements.…”
Section: Statementsmentioning
confidence: 99%
“…Students become critical thinkers when they encounter discussions on home-related studies. Researchers have consistently demonstrated a strong correlation between the educational outcomes of parents and those of their children (Lim, 2021). However, Correlation cannot define the cause of performance; other factors like parental support, a conducive home learning environment, access to resources such as technology, and extra-curricular activities can be the foundation and cause of students' academic achievements.…”
Section: Statementsmentioning
confidence: 99%
“… 49 Moreover, parents with higher education, especially those who have received college and above, tend to receive more cultural and social capital in the process of studying, and naturally can provide their children with better and richer education-related information, making it easier for children to form higher educational expectations. 50 In addition, the higher the family income, the more parents will want their children to receive a higher level of education. 51 Higher social values can be realized through education, and the family’s economic status can be maintained even improved.…”
Section: Advance Research and Theoretical Assumptionsmentioning
confidence: 99%
“…This proposes that the more families support their kids' learning and instructive advancement, the more their kids will in general do well in school and proceed with their schooling. Most researchers have indicated that the impact that parents can have on their children's learning and achievement transcends income levels and social status (Lara & Saracostti, 2019;Lim, 2021). The most accurate predictor of a student's academic accomplishment, according to Fuudia (2019), is the amount to which that student's family is able to build a positive home environment that inspires learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in Ghana, there has not been any conscious effort on the part of the government to come out with a clear policy or white paper or a fiat of the sort (Fuudia, 2019). Notwithstanding this, some parents have continuously participated meaningfully in augmenting their children's scholastic advancement in the area of good home nurturing, supervision and monitoring of child school progress, and school governance (Fuudia, 2019;Lim, 2021;Oluwatelure & Oloruntegbe, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation